2021
DOI: 10.1039/d1ce00333j
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical studies of a room temperature phosphorescent Cd(ii) based MOF and its application towards ratiometric detection of Hg2+ ions in water

Abstract: A new cadmium based MOF [Cd(C5N1S1H4)(C6O5H3)] (C5N1S1H4 = 4MPy, C6O5H3 = HFDA), Cd_1, was synthesized by solvothermal reaction using 2,5-furandicarboxylic acid (H2FDA) and 4-mercaptopyridine (4MPyH) formed in situ by the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…356,357 Despite the fact that metal-organic frameworks cannot be considered true organic polymers, we should mention a number of studies in which FDCA and furoic acid were used as ligands, which allows the preparation of MOFs with different applications from photocatalytic/photosensitive/luminescent activity to single-molecular magnets and metal ion detectors. [358][359][360][361][362][363][364][365][366] Finally, it was demonstrated that humins, usually regarded as a waste and the product of furans and carbohydrate tarring, can also be considered a new class of thermoset materials and composite matrices. 367…”
Section: Scattered Materialsmentioning
confidence: 99%
“…356,357 Despite the fact that metal-organic frameworks cannot be considered true organic polymers, we should mention a number of studies in which FDCA and furoic acid were used as ligands, which allows the preparation of MOFs with different applications from photocatalytic/photosensitive/luminescent activity to single-molecular magnets and metal ion detectors. [358][359][360][361][362][363][364][365][366] Finally, it was demonstrated that humins, usually regarded as a waste and the product of furans and carbohydrate tarring, can also be considered a new class of thermoset materials and composite matrices. 367…”
Section: Scattered Materialsmentioning
confidence: 99%
“…MOFs are generally synthesized via solvothermal techniques. [108][109][110][111][112] But mechanochemical methods, [113][114][115][116] electrochemical routes, [117][118][119][120] sonochemical routes, 121-124 microwave-assisted syntheses, [125][126][127][128] and slow-layer diffusion techniques [129][130][131][132][133] are also used for the preparation of MOFs. In MOFs, the pore size and surface area can be tuned by using suitable ligands as the linkers.…”
Section: Composite Supercapacitorsmentioning
confidence: 99%
“…Luminescence-based detections have drawn attention due to their quick response time, high perceptivity, and ease of operation along with portability. Various kinds of materials such as organic dyes, quantum dots, metal nanoclusters, conjugated polymers, and supramolecules are reported for the detection of this anion. However, these materials suffer from some disadvantages like poor water solubility, toxicity, laborious synthesis, and poor stability. Consequently, metal–organic frameworks, consisting of inorganic metal or metal oxide nodes and organic polydentate bridging ligands with excellent porosity, large surface area, high thermal stability, and diverse structures, are extensively applied in many areas such as smart sensing, hydrogen storage and separation, drug delivery, nonlinear optics, magnetism, proton conductivity, supercapacitor, catalysis, and energy storage. The luminescence properties of MOFs have been extensively used for the sensing experiment of various types of analytes, as the luminescence properties are very much dependent on their physical features and interaction with analytes via the hydrogen bond, coordinate bond, pi–pi interaction, electron transfer, and energy transfer. Due to different coordination environments, variable oxidation states, formal charges of metal ions, and different binding sites of ligands, MOFs are very useful for the purpose of discernment even at the atomic extent. …”
Section: Introductionmentioning
confidence: 99%